Assessing Influence of HIV Status on Management outcomes of Drug Sensitive Pulmonary Tuberculosis in the Bo District of Southern Sierra Leone. - Allieu, Tommy (International Journal of Health Sciences, 2023)
Purpose: Tuberculosis in Human immunodeficiency virus is a predictor of unfavourable outcome during the management of TB cases due to the synergy both bear in the patient. This study is to test the hypothesis that patient is more likely to be unfavourable in the co infected than the TB stand-alone patients with standard treatment in patients. The associated factors might not be exhaustive that leads to outcomes factored in the study. Methodology: The retrospective cohort study data of 1,947 patients admitted from 1st January 2020 to 1st January 2022 at TB treatment centres in Bo district of Sierra Leone was analysed using datatab software after data completeness was checked and cleaned. Both bi-variable and multi-variable logistics regression and other statistical methods were employed to assess the relationship between HIV+TB synergic as well as TB alone outcomes. Data was analysed based on 95% CI and p<0.05. Findings: When an ANOVA was used to test for significance from zero, F=3.41, p = 0.002, R2 = 0.01. Regression coefficients for exits = 1.17 - 0.02., gender =-0.02, literacy = -0.1, family bread winner with TB= -0.02 and foods insecurity = +0.07. A point-biserial correlation was also computed to determine the relationship between HIV status and TB interms of outcome which showed a positive correlation between HIV status and exit code information, although no statistically significance (rpb = 0.04, n = 1987, p = .065). Unique contribution to theory, practice and policy: Successful treatment outcome was high among HIV/TB co-infected as well as TB mono-infected should both be treated with standard treatments. Strengthening patient management in a collaborative approach and use of novel drugs as well as research will increase the survival rate of patients treated. With standard treatment and patient centered care the outcome of TB patient management will not be hinged on their HIV status. The adoption of this theory into policy in TB programmes will improve the success rate in TB management.